ANTHROPOLOGICAL OVERVIEW OF THE CONCEPT OF TURKISH HEART GEOGRAPHY (Third Sector Social Economic Review, 2019)
Considering the fact that during known history process the Turks starting from Central Asia; have spread to China, India, Russia and European geography and during the Ottoman Empire, they expanded it into Africa the boundaries of the “Turkish Heart Geography” occur spontaneously. The limits to be defined are further expanded when evaluated in addition to the 380 million Turkish population living in the world, 1 billion 800 million Muslims and also non-Turkish nations and communities that have connected with the Turks. This geographical area with a common background has always felt the need for union.It is not possible to define this geography with today's international relations concepts. The concept of “Heart of Bounds”, which does not have the exact equivalent in many languages and seems to have been created to describe the links between the Turks and their geography. With thousands of years of experience from the depths of Asia, the Turks have established a bridge and have succeeded in fusing and synthesizing the cultures where they have gone.There is tolerance on the basis of this, there is humanity and above all there is justice. It is for this reason that in the hardest days of the Turkish War of Independence, this volunteer geography stood up and supported the Turks with the help they collected and morally supported.Today, the power gap in the region where the Turks were withdrawn could still not be filled. Disruption of order in the world began in the period with the deterioration of integrity in the geography of the Turks and it is clear that there is a need to re-establish the cultural bond in the Turkish geopolitics.In these regions today's international system, leaving the people back, not bringing happiness and unjusted projects. Contrary to this in the case of the creation of joint projects with equal, fair, mutual aid, co-development, acculturation and peace and prosperity of the people and neighbors of the region it is thought that the reestablishment of peace and the systems that will make the whole region happy can be created.In this article, while given some of the information about the formation of Turkish Heart Geograpy during the historical development, on the other hand peaceful cultural and economic unity projects is going to defined that can be developed.
Keywords: Heart Geography; Culture; Heart Bounds; Anthropology; History; World Order; Common Background.